Meningococcal Carriage: Epidemiology, Causative Agent, Inducing of Immune Protection - N. N. Kostyukova; V. A. Bekhalo (Эпидемиология и вакцинопрофилактика)
A review of the actual problems concerning the meningococcal carriage is presented. The review includes: the epidemiological features of meningococcal carriage, the phenotyping and genotyping characteristics of the carriage strains, the modern models of the carriage, the general and local (mucosal) immune protection induced by the carriage. The significance of genetic and virulence heterogenicity of carriage meningococcal population is underlined.